2016
DOI: 10.3917/rhu.045.0087
|View full text |Cite
|
Sign up to set email alerts
|

Installer un lycée dans sa ville (1830-1880)

Abstract: Au cours du XIX e siècle, en France, l’État prend progressivement à sa charge des établissements d’enseignement secondaire précédemment gérés par des municipalités. C’est une mesure recherchée par les villes mais les moyens financiers alloués à cette politique sont limités. Ceci implique que deux villes d’un même département ne peuvent voir leur établissement érigé en établissement national. Cette situation engendre des concurrences entre les principales villes de treize départements. Par l’étude à l’échelle l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This approach is associated with interesting results such as improving the mechanical properties, adding new characteristics, such as electrical properties, or controlling of the phase morphology. [8][9][10][11][12][13][14] For example, Elias et al reported that silica nanoparticles induced a decrease in the effective interfacial tension between polypropylene (PP) and ethylene vinyl acetate phases and thereby a lower particle size for dispersed phase. [15] In another work, Palacios et al concluded that the fine-tuned morphology of the PP/polyamide-6 (PA-6) blends with enhanced ductility and barrier properties can be obtained at an optimum content of nanosilica and compatibilizer.…”
Section: Introductionmentioning
confidence: 99%
“…This approach is associated with interesting results such as improving the mechanical properties, adding new characteristics, such as electrical properties, or controlling of the phase morphology. [8][9][10][11][12][13][14] For example, Elias et al reported that silica nanoparticles induced a decrease in the effective interfacial tension between polypropylene (PP) and ethylene vinyl acetate phases and thereby a lower particle size for dispersed phase. [15] In another work, Palacios et al concluded that the fine-tuned morphology of the PP/polyamide-6 (PA-6) blends with enhanced ductility and barrier properties can be obtained at an optimum content of nanosilica and compatibilizer.…”
Section: Introductionmentioning
confidence: 99%
“…Improvement of the properties of polymer blends by adding clay nano-particles have been studied recently. [1][2][3][4][5][6][7][8] Clays have long been used as fillers in polymer materials because of low cost and the improved thermal and mechanical properties of the resulting nanocomposites. [9][10][11][12][13][14] In the present contribution, we will report on an attempt to prepare nano-blends based on poly (ethyl methacrylate) and cellulose acetate butyrate (PEMA/CAB) blends via solution intercalation method using THF as solvent, in the presence of different loadings of Algerian bentonite, purified and organically modified by hexadecyltrimethylammonium chloride (OMMT).…”
Section: Introductionmentioning
confidence: 99%